Assessing fire-blocking effectiveness of barrier fabrics in the cone calorimeter. (July 2019) - Nazare, Shonali; Pitts, William M.; Shields, John; Knowlton, Elizabeth; De Leon, Benito; Zammarano, Mauro; Davis, Rick
Cone calorimetry experiments of on flexible polyurethane foam and flexible polyurethane foam covered with a variety of fire-blocking barrier fabrics were used to characterize and rank the effectiveness of barrier fabrics with the ultimate goal being an ability to predict the effectiveness of barrier fabrics for reducing the flammability of residential upholstered furniture. The primary measure used to characterize the burning behavior was heat release rate. The effect of the underlying sample substrate was shown to have a large effect on the burning behavior of flexible polyurethane foam samples, and a thermally insulating substrate was used during composite experiments. At times, rapid heat release rate fluctuations were observed, and in such cases approximate corrections were applied to correct for finite cone calorimeter time response. Measurements using thermocouples placed within the flexible polyurethane foam provided insights on flexible polyurethane foam pyrolysis behavior, the collapse rate of flexible polyurethane foam, and the thermal protective properties of barrier materials. Heat release rate temporal profiles for flexible polyurethane foam showed two distinct burning stages with peak values which have been attributed to sequential burning of species (primarily) derived from the diamine ( PHRR 1 ) and polyol components ( PHRR 2 ) used to manufacture the flexible polyurethane foam. When a barrier fabric was added, many of the composites displayed a three-stage burning behavior which was attributed to an initial short, intense burning (termed flash burning) stage associated with the barrier fabric covering followed by the two flexible polyurethane foam stages. Seven out of 16 flexible polyurethane foam/barrier fabric composites exhibited flame extinction prior to fuel burn out. Five out of the seven composites reignited when the spark ignition source was reapplied. Reignition allowed barrier fabric effectiveness to be assessed even for cases with flame extinction. Barrier fabric performance was shown to be consistent with four properties that were previously identified as important barrier fabric properties: barrier fabric flammability, gas permeability, thermal protection, and physical integrity. In addition, the current experiments indicate the presence and effectiveness of gas-phase active flame retardants in the barrier fabric can also play an important role. A limited number of tests were conducted to de-couple the effects of flame-retardant chemicals and physical effects of barrier fabrics on flexible polyurethane foam burning behavior. These tests showed that while flame-retardant chemicals can be effective in quenching and extinguishing the flames, the presence of effective barrier fabric shells is also very important in lowering the heat release rate of burning flexible polyurethane foam. In general, the presence of a barrier fabric was shown to reduce the heat release rate peak values during both flexible polyurethane foam burning stages. The magnitude of the peak associated with second-stage flexible polyurethane foam burning was deemed the most appropriate for characterizing the thermal protection provided by a barrier fabric. Since the times for PHRR2 also varied between composites, a measurement referred to as the p eak fi re g rowth ra te (PFIGRA) parameter was calculated by dividing the heat release rate by time since time to ignition and PFIGRA2 was also considered for characterizing the barrier fabrics. Three possible classification schemes, each consisting of three classes, were introduced based on composite flame extinction and reignition behavior, PHRR2 values, and PFIGRA2 values. Each scheme provided differentiation between barrier fabric effectiveness. While the schemes were able to assess whether the barrier fabrics were particularly effective or ineffective, there were variations among classes of barrier fabrics having intermediate levels of effectiveness. Further work will be required to assess which, if any, of the classification schemes are most appropriate for predicting barrier fabric performance in residential upholstered furniture.